Multi-omics integration method based on attention deep learning network for biomedical data classification. (April 2023) - Gong, Ping; Cheng, Lei; Zhang, Zhiyuan; Meng, Ao; Li, Enshuo; Chen, Jie; Zhang, Longzhen
Highlights: Proposed a novel end-to-end Multi-omics attention deep learning network (MOADLN) for biomedical data classification. MOADLN jointly explores the correlation between patients in intra-omics and the correlation of cross-omics in the label space. Construct the patient correlation via self-attention in the latent feature space for omics-specific feature learning. Abstract: Background and objective: Integrating multi-omics data for the comprehensive analysis of the biological processes in human diseases has become one of the most challenging tasks of bioinformatics. Deep learning (DL) algorithms have recently become one of the most promising multi-omics data integration analysis methods. However, existing DL-based studies almost integrate the multi-omics data by concatenation in the input data space or the learned feature space, ignoring the correlations between patients and omics. Methods: We propose a novel multi-omics integration method, called Multi-omics Attention Deep Learning Network (MOADLN), which is used for biomedical data classification. Firstly, for each type of omics data, we use three fully-connected layers and the self-attention mechanism to reduce dimensionality, and construct the correlations between patients, respectively. Then, we apply the feature vector learned from self-attention to generate the initial category labels. Secondly, for the initial label predicted of each omics data, we use an effective Multi-Omics Correlation Discovery Network (MOCDN) to learn the cross-omic correlations in the label space. Finally, we use the softmax classifier for label prediction. Results: We demonstrate that our method outperforms several state-of-the-art methods on two datasets with mRNA expression data, DNA methylation data, and miRNA expression data. In addition, we identified essential biomarkers of relevant diseases by MOADLN, and the generality of MOADLN is also demonstrated in the KIRP and KIRC datasets. Conclusions: MOADLN jointly explores correlations between patients in intra-omics and correlations of cross-omics in label space, which is an effective DL-based classification of biomedical data.